Article RETRACTED due to manipulation by the authors Content validity and reliability of agility test in wheelchair tennis - Abdul Alim; Tomoliyus Sumardi; Cerika Rismayanthi; Wahyu Dwi Yulianto; Mohd Izwan Shahril (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose. This study aims to develop the construction of an agility test in wheelchair tennis. Material and methods. This research is a research development consisting of four stages. In the first stage, documents and research journals were analyzed to develop the construction of a wheelchair tennis agility test. The first step resulted in six aspects, namely: the definition of the agility test motion aspect, the suitability of the test to the state of the match aspect, ease in the agility test aspect, reliability aspect, clarity instructions on the image aspect, and security aspect. The Delphi technique was used in the second stage, and experts assessed the results of constructing the wheelchair tennis agility test in the first stage. In the third stage, the results of expert judgment with the Aiken formula were analyzed to test the validity of the contents. Participants in this study were documents and seven experts consisting of five national coaches and two experts with Doctoral degrees in tennis science specifications. The fourth step with Cronbach’s Alpha reliability test and Intraclass Correlation Coefficient was tested on 16 experienced wheelchair athletes, male and female, with the age of 18-40 years and an average training level of 11.20±1.7 years.Results. The validity test results on aspect 1 show V value of 0.78; on aspect 2 show V value of 0.90; on aspect 3 show V value of 0.85; on aspect 4 show V value of 0.96; on aspect 5 show V value of 0.96; and on aspect 6 show V value of 0.96. The result of Croncbach’s Alpha reliability test is 0.804, and the value of the Intraclass Correlation Coefficient is 0.804. Then, the agility test of wheelchair tennis athletes has a valid and reliable value.Conclusions. The wheelchair tennis agility test construct has high validity and reliability. The construction document of the wheelchair tennis agility test instrument shows that it has high content validity and reliability, so it can convince readers and researchers about the instrument. Further research requires more detailed testing of retest test conducted with larger samples.